Encephalopathy Associated with Severe Cytomegalovirus Infection in an Immunocompetent Young Woman - Tetsuka, Syuichi (Case Rep Infect Dis, 2021)
Primary cytomegalovirus (CMV) infection in healthy young adults is usually an asymptomatic or mononucleosis-like syndrome, whereas in immunocompromised patients, CMV can cause significant disease. In this study, we report an unusual case of primary CMV infection wherein the patient, an immunocompetent 21-year-old woman, presented severe encephalopathy, acute hepatitis, retinitis, and reactivation of latent Epstein–Barr virus. She developed confusion, high fever, headache, and tonic-clonic seizures. Brain magnetic resonance imaging showed high-intensity lesions in the medial temporal lobe and basal ganglia. Liver dysfunction was observed, and abdominal computed tomography revealed splenohepatomegaly. After fundus findings, the patient was diagnosed with CMV retinitis. Upon admission, she was treated with intravenous acyclovir and steroid pulse therapy. Considering both her serious clinical condition and elevated serum levels of interleukin-6, we speculated that her condition was similar to cytokine-storm-induced encephalopathy. On day 2 after admission, she showed prompt recovery from these clinical manifestations. Since blood CMV pp65 antigenemia was found to be positive, we administered ganciclovir for 2 weeks. On the basis of her clinical manifestations and the presence of blood CMV DNA and CMV pp65 antigenemia along with IgM kinetics, we finally diagnosed this patient with severe primary CMV infection. She left our hospital without sequelae 20 days after admission. The incidence of severe CMV disease in immunocompetent young adults might be higher than previously recognized. Noninvasive testing for CMV (such as CMV pp65 antigenemia and CMV DNAemia) is widely available and can help early diagnosis. Short-term glucocorticoid therapy might be beneficial in the treatment of encephalopathy in the early stages of primary CMV infection. Considering such a background, clinicians should keep severe primary CMV infection in mind as a differential diagnosis in the clinical setting.